Analysis of Leadership Style and Remuneration System According to The Perception Of Human Resources In Radiological Installation In Dr. Soepraoen Malang Hospitals - Priawan, Hendra; Siyoto, Sandu; Nurwijayanti, Nurwijayanti (Journal for Research in Public Health, 2019)
Human resources in an institution such as a hospital are an important strategy to create an accelerated improvement in overall health status, integrated, equitable, affordable and acceptable to the entire community. In maintaining the continuity and life of its organization, organizations are required to be able to maintain good relations between the leaders of the organization and human resources as the driving force of an organization. This research was conducted by taking the object of research in the installation of radiology at the Army Hospital Dr. Soepraoen, Malang City. This study aims to determine the perceptions of human resources (HR) from Radiology Installation in Army Hospital Dr. Soepraoen Malang towards leadership style and remuneration system. The method used in this study is qualitative research with a descriptive approach. The sampling technique that will be used in this study is a total sampling of 15 radiology installation employees at the Army Hospital Dr. Soepraoen. The results of the study show that a good perception of Human Resources (HR) related to Leadership Style in the Installation of Army Hospital Radiology dr. Soepraoen Malang and the application of remuneration carried out by Army Hospital Dr. Soepraoen Malang city runs well. Advice from researchers is expected to be able to develop knowledge in the field of administration and quality of hospital services. In addition, this research might be able to help further similar research, especially with regard to the remuneration system and leadership style in hospitals.